Faktor Budaya dan Perilaku Keluarga dalam Pencegahan Penularan TB Paru di Wilayah Nusa Tenggara Indonesia - Mulu, Servasius To'o Jala (JURNAL KESEHATAN PRIMER, 2022)
Background: Tuberculosis (TB) remains a major global health issue, with Indonesia being one of the countries with the highest number of TB cases. In East Nusa Tenggara (NTT), particularly in Kupang City, the lack of public knowledge about TB continues to be a significant health problem. One of the key factors in preventing TB transmission is the role of the family, which is often influenced by cultural factors and behaviors. The negative stigma surrounding TB patients and misconceptions related to cultural beliefs, such as reliance on traditional medicine or mystical understandings of the disease, further hinder effective TB control. Objective: This study aims to examine the cultural factors and family behaviors in preventing the transmission of TB in East Nusa Tenggara, Indonesia. Methods: This study employed a literature review methodology, analyzing relevant journals published between 2019 and 2022. The research process involved problem identification, searching for journals using relevant keywords, article selection, and summarizing the findings. The PICO (Population, Intervention, Comparison, Outcome) approach was used to analyze the relationship between cultural factors, family behaviors, and TB transmission prevention. Results: The findings indicate that cultural beliefs and practices in East Nusa Tenggara significantly influence family behavior in preventing TB. Many families prefer traditional medicine or associate TB with mystical causes, such as curses or hereditary diseases, which hinders proper treatment and efforts to prevent transmission. Limited knowledge, especially about the symptoms and prevention of TB, exacerbates the situation. Additionally, low levels of education and limited access to information contribute to families' lack of awareness in supporting treatment and preventing the spread of TB. These findings highlight the importance of culturally sensitive health education to enhance the role of families in TB prevention.